Microbial species richness under spontaneous plant colonisation in copper mine tailings - Lazaro, JEH; Sioson, EJ; Aja, JA; Dayap, J; Salandanan Bautista, K; Tanciongco, AM; Gervasio, JHC; Quierrez, RNM; Samaniego, JO; Arcilla, CA; Quimado, MO; Newsome, L; et al. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
We aimed to assess the species richness of the microbial communities in copper mine tailings that have been spontaneously colonised by plants. We characterised the bacterial (16S rRNA, or 16S) and fungal (ITS) sequences from samples taken from a single bench of an undisturbed mature tailings storage facility (TSF1) and samples from a reference site (Ref Site) located 1 km away. In all sampling sites, the dominant plant was a single species of grass (Saccharum spontaneum); a few other species were sometimes found with the grass in TSF1. Amplicon sequence variants (ASVs) were deduced using DADA2 from 16S rRNA gene (bacteria) and ITS2 (fungi) amplicons. Rarefaction curves suggested that the TSF1 had more ASVs on average than the Ref Site; furthermore, the TSF1 appeared to have more ASVs than were sampled. The Chao1 and Faith indices for both bacteria and fungi were higher for the TSF1 tailings. Similar bacterial orders were found in both sites, including common groups, although Rhizobiales were more common in TSF1 and Chloroflexi in the Ref Site. The most abundant bacteria found belonged to the phyla Proteobacteria, Chloroflexota, Acidobacteriota and Actinomycetota. Overall fungal diversity began to increase with plant diversity.PICRUSt2 analysis of predicted metabolic pathways showed more potential pathways at the TSF1. These results suggest a relation between microbial species richness and plant colonisation, and that succession towards greater species richness is taking place. This study may provide a baseline against which the effect of any rehabilitation intervention on the soil can be measured.
Keywords: mine tailings